On the EU-US Current Account - Gabriel Felbermayr; Martin Braml (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
The first part of this short report uses the newest available data from the Bureau of Economic Analysis (BEA), an agency of the US Department of Commerce, to analyse economic relations between the US and the EU. The data is used to decompose the components of the US current account balance, and to analyse the bilateral balance of payments with the European Union, the Euro Zone and Germany. In the second part, we use data provided by Eurostat to mirror US figures. We find enormous discrepancies between what the EU and the US report, particularly with respect to primary income.
Keywords: 330